(untitled) (MAUSAM, 1966)
Dispersion of surface waves of Ray1eigh type due to two earthquake shocks in the Arctic region was studied from the seismograms of Shillong. From the study of the dispersion curves it was concluded that the average crustal thickness was of the order of 45 km for the Asian path from Arctic to Shillong.